Strategi Penguatan Sistem Penanganan Kebakaran Diperkotaan - hakim, Abdul; Basriman, Iman; Gusdini, Ninin Gusdini (Dian Nuswantoro Semarang, 2023)
Fire is a condition of a building, such as a house, factory, market, or building, burning uncontrollably, causing casualties. Fire is one of the disasters caused by non-natural factors. The purpose of this study is to analyze internal and external environmental factors in fire prevention. As well as designing a strategy formulation in fire prevention prevention. The method used in this research is SWOT analysis using the QSPM (Quantitative Strategy Planning Matrix) matrix. The number of respondents who were taken in this study were three people. The results of this study are based on interviews with the fire department which resulted in factors influencing the occurrence of fires from internal and external during the fire fighting strategy. The most influential internal factor in terms of strength is the formation of early handling officers at the RW level to provide counseling to the community. Already has a lot of fleet facilities. Lack of training for new firefighters. External factors on fire prevention include. Provide external training for firefighters who are in the agency/community while in terms of threats, namely weak cooperation with electricity, water providers. Strategies that can improve fire prevention include increasing fire prevention capacity building for the community and agencies and residents maximizing early fire prevention so that fires are immediately extinguished